2016
DOI: 10.1186/s12870-016-0927-9
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of flax (Linum usitatissimum L.) under edaphic stress

Abstract: BackgroundCultivated flax (Linum usitatissimum L.) is widely used for production of textile, food, chemical and pharmaceutical products. However, various stresses decrease flax production. Search for genes, which are involved in stress response, is necessary for breeding of adaptive cultivars. Imbalanced concentration of nutrient elements in soil decrease flax yields and also results in heritable changes in some flax lines. The appearance of Linum Insertion Sequence 1 (LIS-1) is the most studied modification. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 36 publications
0
25
0
1
Order By: Relevance
“…The expression levels of target genes were normalized to those of the reference genes. Finally, relative (T/N) expression level of target genes was calculated using the ΔΔCt method [ 24 ]. Since the relative inner variability between the calculated mRNA levels of the reference genes was found to be less than two-fold, a variation in the expression of the target genes of two-fold or greater was considered to be significant.…”
Section: Methodsmentioning
confidence: 99%
“…The expression levels of target genes were normalized to those of the reference genes. Finally, relative (T/N) expression level of target genes was calculated using the ΔΔCt method [ 24 ]. Since the relative inner variability between the calculated mRNA levels of the reference genes was found to be less than two-fold, a variation in the expression of the target genes of two-fold or greater was considered to be significant.…”
Section: Methodsmentioning
confidence: 99%
“…[19] qPCR data were analyzed using the relative quantification (ΔΔCt) method. [20,21] Relative mRNA level of the genes was calculated using ATG program compatible with relative quantification software (Thermo Fisher Scientific, USA). [22] At least 2-fold mRNA level changes were considered as significant.…”
Section: Tissue Samplesmentioning
confidence: 99%
“…Expression analysis allows scientists to identify genes that are expressed in particular flax tissues (Day et al, 2005; Venglat et al, 2011; Zhang and Deyholos, 2016). Moreover, the responses of flax to drought (Dash et al, 2014), salinity, and alkalinity stresses (Yu et al, 2016), nutrient imbalance (Dmitriev et al, 2016), and Fusarium oxysporum infection (Wojtasik et al, 2015, 2016) have been studied and stress-responsive genes identified.…”
Section: Introductionmentioning
confidence: 99%